Comprehensive analysis of tumor microenvironment cytokines in Waldenstrom macroglobulinemia identifies CCL5 as a novel modulator of IL-6 activity - Elsawa, Sherine F. (American Society of Hematology, 2011)
Although proinflammatory and chemotactic cytokines can profoundly affect the tumor microenvironment, and many of them have been shown to have therapeutic efficacy in preclinical models, the role of these molecules in Waldenström macroglobulinemia (WM) remains poorly understood. In this study, simultaneous analysis of WM patient sera and bone marrow biopsies identified a set of dysregulated cytokines including CCL5, G-CSF, and soluble IL-2 receptor, that were significantly elevated in WM patients whereas IL-8 and EGF levels were significantly lower in these patients compared with healthy controls. Interestingly, CCL5 levels positively correlated with features of disease aggressiveness such as elevated IgM levels and bone marrow involvement. Functional analysis of tumor microenvironment revealed a functional correlation between CCL5 levels and IL-6 levels, a proinflammatory cytokine with an important role in normal and malignant B-cell biology. Furthermore, CCL5 stimulated IL-6 secretion in WM stromal cells resulting in increased IgM secretion by WM malignant cells via the JAK/STAT signaling pathway. Thus, together these results define a novel signaling network in the WM tumor microenvironment controlling IgM secretion and suggest CCL5 as a potential target for the treatment of this disease.